Stress levels and menstrual cycles in high school adolescents - Saldinar, Alena Briliantyas; Athiah, Medina; Hasanah, Yulisnawati; Nurwanny, Raissa; Aditiawati, Aditiawati (Indonesian Pediatric Society, 2025)
Background Around 15.5 million (34.9%) adolescents in Indonesia experience stress. Most of the stress in adolescents comes from internal and external academic demands. One of the negative impacts of stress is the disruption of hormonal mechanisms in the female reproductive system, which can affect the menstrual cycle. Objective To analyze the relationship between stress level and menstrual cycle in adolescent girls aged 15 - 17 years who have menses ≥ 2 years. Methods This study used primary data from instruments such as the Depression Anxiety Stress Scale (DASS 42) questionnaire modified by Damanik and the menstrual cycle questionnaire by Aldiba filled on Google forms by 1,565 adolescents from four high schools in Palembang City. We also excluded adolescents with conditions that could potentially bias the study, such as endocrine diseases (pituitary tumors and Cushing's syndrome), athletes with intensive physical activity, use of hormonal drugs, and abnormalities in nutritional status. Results A total of 281 of 961 respondents who met the inclusion criteria were randomly selected through a stratified proportional random sampling method. Of those who reported experiencing stress, 27% experienced moderate stress. The majority of subjects experienced menstrual cycle disorders (55.5%). Adolescents with moderate stress level and above had a greater percentage of menstrual cycle disorders compared to adolescents who did not experience stress (P=0.039). Severe levels of stress were significantly associated with menstrual cycle irregularities (P=0.025) Conclusion Stress levels are significantly associated with menstrual cycle irregularities among high school adolescents in Palembang City.